2012
DOI: 10.1002/biot.201100480
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening for cellobiose dehydrogenases by Prussian Blue in situ formation

Abstract: Extracellular fungal flavocytochrome cellobiose dehydrogenase (CDH) is a promising enzyme for both bioelectronics and lignocellulose bioconversion. A selective high-throughput screening assay for CDH in the presence of various fungal oxidoreductases was developed. It is based on Prussian Blue (PB) in situ formation in the presence of cellobiose (<0.25 mM), ferric acetate, and ferricyanide. CDH induces PB formation via both reduction of ferricyanide to ferrocyanide reacting with an excess of Fe³⁺ (pathway 1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…YNB-CAA /Gal plates with grown colonies were used and 20mL of molten 2% agar containing 0.15mM cellobiose, 0.78mM K3[Fe(CN)6] and 0.16mM NH4Fe(SO4)2 in 0.1 M Na-acetate buffer (pH 4.0), cooled to 40ᵒC was added [22]. After cooling, the plates were incubated 4h at room temperature and monitored for CDH producing transformants were identified by the presence of colorless halo around the S.cerevisiae colonies on plates overlaid with DCIP, resulting from CDH activity.…”
Section: Agar Plate Assaymentioning
confidence: 99%
“…YNB-CAA /Gal plates with grown colonies were used and 20mL of molten 2% agar containing 0.15mM cellobiose, 0.78mM K3[Fe(CN)6] and 0.16mM NH4Fe(SO4)2 in 0.1 M Na-acetate buffer (pH 4.0), cooled to 40ᵒC was added [22]. After cooling, the plates were incubated 4h at room temperature and monitored for CDH producing transformants were identified by the presence of colorless halo around the S.cerevisiae colonies on plates overlaid with DCIP, resulting from CDH activity.…”
Section: Agar Plate Assaymentioning
confidence: 99%
“…Acceleration of heterosidic bond hydrolysis in MUG 4 can be monitored by fluorophore liberation with high accuracy in both continuous and discontinuous assays, whereas hydrolysis of holosidic bonds can be quantified by coupled CDH‐based high troughput assay with an appropriate one‐electron acceptor to increase sensitivity, as described here or in refs. . Just a gentle decrease in the MUG 4 nonproductive binding by fine tuning of A1 loop structure is expected to increase the turnover number of 1,4‐β‐glucosidic bond hydrolysis by an order of magnitude making Cel7A more close to Cel7B that shares the same catalytic mechanism, same structural and dynamic behavior at site −2, and strictly conserved amino acid residues involved in the formation of glycosyl‐enzyme at site −1 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quinones can give confounded results due to their spontaneous oxidative side reactions in the alkaline pH range [18]. Recently, ferricyanide was used in a high-throughput screening assay that is based on the formation of Prussian Blue, but it was shown that this assay is highly specific for CDH while other flavin-dependent carbohydrate oxidoreductases (glucose oxidase, PDH) do not show similar reactions [25]. …”
Section: Discussionmentioning
confidence: 99%